A bad day for pretty [large type] - Littlefield, Sophie (Thorndike Press large print mystery, 2010)
Stella Hardesty, avenger of wronged women, is getting cozy with Sheriff ʺGoatʺ Jones when a tornado blows Goat's scheming ex-wife through the front door. Adding to the chaos, the snack shack at the demolition derby track is destroyed, unearthing a woman's body. The main suspect in the murder is Neb Donovan, who laid the foundation. But Stella doesn't believe the gentle man could kill anyone, and promises his frantic wife she'll look into it.